Nationalism reframed nationhood and the national question in the New Europe - Brubaker, Rogers (Cambridge Cambridge University Press, 1996)
Nationalism Reframed is a theoretically and historically informed study of nationalism in Eastern Europe and the former Soviet Union. Rogers Brubaker develops an original account of the interlocking and opposed nationalisms of national minorities, the nationalizing states in which they live, and the external national homelands to which they are linked by external ties. He then analyzes contemporary nationalisms in historical and comparative perspective, tracing the parallels between the Eastern European nationalisms of today and those of the interwar period.
Includes bibliographical references.
Keywords: Nationalism -- Europe